Graptopetalum sinaloensis (Crassulaceae), a new species from Sinaloa, Mexico - Vega Aviña, Rito; Delgado Vargas, Francisco; Pío León, Juan Fernando (Instituto de Ecología, A.C., 2020)
Background and Aims: The genus Graptopetalum includes about 20 species of branched or acaulescent rosette herbs that develop in little accessible semiarid environments (mountains or ravines) of Mexico and Arizona. The authors have developed continuous work to document the flora of Sinaloa and the present article reports a taxonomic novelty in the genus Graptopetalum. Methods: In the municipality of Culiacán, Sinaloa, Mexico, a small population of plants of the genus Graptopetalum with dry inflorescences was found in June 2013, and some plants were collected and cultivated, they flowered in March. Plants with flowers were collected from the same location in February 2014. Morphological data of wild and cultivated material were compared with that of herbarium specimens, literature, and cultivated Graptopetalum species; and it was determined that collected material is a new species for science. Key results: The new taxon Graptopetalum sinaloensis, section Graptopetalum, is described. Its differences and similarities with the closest species are discussed. Moreover, a new and updated dichotomous key is provided for the eight species of this section. Conclusions: Graptopetalum sinaloensis is endemic to south-central Sinaloa, Mexico. It grows in very localized areas, on rocky walls of streams and at the foot of hills, forming small populations in reduced areas of 5 to 10 m2. Graptopetalum sinaloensis differs from other Graptopetalum species from Sinaloa by its 5-merous flowers vs. G. rusbyi with 6-7-merous ones, and by its paniculate inflorescence vs. G. occidentale with cymose ones. Additionally, the geographical distribution of the three species does not overlap.